2015
DOI: 10.1167/iovs.15-17485
|View full text |Cite
|
Sign up to set email alerts
|

The Associations of Dietary Intake of Polyunsaturated Fatty Acids With Diabetic Retinopathy in Well-Controlled Diabetes

Abstract: Increasing PUFA intake was associated with a reduced likelihood of the presence and severity of DR in well-controlled diabetes, whereas increasing SFA intake was associated with an increased likelihood of the presence and severity of DR. Further studies to confirm this observation are warranted to elucidate the underlying mechanisms and potential role of dietary PUFA and SFA intake in the management of DR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 33 publications
3
83
0
Order By: Relevance
“…Actually, a small cross-sectional study reported that increased PUFA intake (although not distinguishing between ω-3 or ω-6 fatty acids) was associated with reduced odds of prevalent DR and lesser DR severity in patients with well-controlled diabetes, while no associations were found for those poorly controlled. 22 Suprisingly, neither epidemiologic studies nor clinical trials focused on dietary LCω3PUFA and DR, although the link has repeatedly been proven in experimental models. [8][9][10][11] By reporting that regular LCω3PUFA intake seems to reduce the risk of the most severe form of DR, particularly in patients with hypertension or advanced diabetes, we reinforce the benefits of these particular fatty acid species in a critical population group.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, a small cross-sectional study reported that increased PUFA intake (although not distinguishing between ω-3 or ω-6 fatty acids) was associated with reduced odds of prevalent DR and lesser DR severity in patients with well-controlled diabetes, while no associations were found for those poorly controlled. 22 Suprisingly, neither epidemiologic studies nor clinical trials focused on dietary LCω3PUFA and DR, although the link has repeatedly been proven in experimental models. [8][9][10][11] By reporting that regular LCω3PUFA intake seems to reduce the risk of the most severe form of DR, particularly in patients with hypertension or advanced diabetes, we reinforce the benefits of these particular fatty acid species in a critical population group.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the retrospective analysis of this study, patients with T1D were advised to reduce their total dietary fat to ,30% and the saturated fat to ,10%, as was formerly recommended by the American Diabetes Association. To this day, the evidence for the effect of dietary fat intake on DR incidence and progression remains inconclusive, and a potential positive effect of specific saturated fatty acids (SFAs) and unsaturated fatty acids has been raised (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Similarly, DR was not associated with omega-3 or −6 PUFA levels in our cohort. This is different from saturated fatty acids, for which a positive association with the presence and severity of DR was described [21]. …”
Section: Discussionmentioning
confidence: 97%